2020
DOI: 10.1002/ejhf.1974
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling outcomes in coexisting severe aortic stenosis and transthyretin cardiac amyloidosis

Abstract: Advances in diagnostic imaging have increased the recognition of coexisting transthyretin cardiac amyloidosis (ATTR-CA) and severe aortic stenosis (AS), with a reported prevalence between 8-16%. In this prospective study, we aimed to evaluate the implications of ATTR-CA on outcomes after transcatheter aortic valve replacement (TAVR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 34 publications
5
94
0
Order By: Relevance
“…The first anecdotic reports have questioned the usefulness of aortic valve replacement, even when performed by TAVI. More recent prospective studies in relatively large cohorts of patients with severe AS in the elderly with or without ATTR-AC undergoing TAVI have shown similar short and medium term results regarding overall survival (with a higher risk of hospitalization for HF amongst patients with ATTR-AC) [33,38]. Waiting for further randomized studies, these results suggest that TAVI should not be denied only on the basis of the coexistence of ATTR-AC.…”
Section: Atrial Fibrillation and Anticoagulationmentioning
confidence: 84%
See 1 more Smart Citation
“…The first anecdotic reports have questioned the usefulness of aortic valve replacement, even when performed by TAVI. More recent prospective studies in relatively large cohorts of patients with severe AS in the elderly with or without ATTR-AC undergoing TAVI have shown similar short and medium term results regarding overall survival (with a higher risk of hospitalization for HF amongst patients with ATTR-AC) [33,38]. Waiting for further randomized studies, these results suggest that TAVI should not be denied only on the basis of the coexistence of ATTR-AC.…”
Section: Atrial Fibrillation and Anticoagulationmentioning
confidence: 84%
“…Recent studies have shown that ATTR-AC frequently coexists with severe degenerative aortic stenosis (AS) (prevalence ranging from 8 to 16%) due to the shared epidemiologic substrate and the possible effect of increased myocardial strain of aortic stenosis acting on an underlying amyloidogenetic substrate [38]. The first anecdotic reports have questioned the usefulness of aortic valve replacement, even when performed by TAVI.…”
Section: Atrial Fibrillation and Anticoagulationmentioning
confidence: 99%
“…Recently, several studies have evaluated the prognostic implications of the coexistence of AC-TTR and severe AS in TAVR candidates, showing how amyloidosis would not significantly impact the survival of patients with severe AS, and especially how TAVR intervention would improve outcome in patients in which the two pathologies coexist. 1 , 2 …”
mentioning
confidence: 99%
“…ATTR-CA is diagnosed by cardiac tracer uptake on bone scan and unremarkable serum and urine free light chain assessment. This method was applied in several studies on older AS patients undergoing transcatheter AVR (TAVR) and a prevalence of AS-CA ranging from 8.4% to 16.0% was reported [2,[6][7][8]. AL, the other predominant amyloid protein found in the heart, is rarely detected in severe AS scheduled for TAVR [6]; however, given the immediate therapeutic implications of AL-CA, this subtype always has to be ruled out by urine and serum free light chain assessment if AS-CA is suspected [5].…”
mentioning
confidence: 99%
“…Until recently, prognostic implications as well as effectiveness of AVR in dual AS-CA were unknown. Even futility of AVR was discussed; however, very recently several studies showed equal survival rates of AS-CA and AS alone following TAVR [2,6,7,9], disproving the conception of treatment futility in AS-CA.…”
mentioning
confidence: 99%